Fuzzy Time Series and Data Visualization for Forecasting Sales of Grocery Ingredients - Rahmat Zulfikar Nasution; Sriani Sriani (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The development of information technology is currently increasingly rapid and produces very large amounts of data. Grocery store or also commonly known as UD. Ridho has several problems in determining the availability of basic food ingredients and the amount of demand for goods is uncertain, which means that grocery stores often experience shortages of supplies and/or excess supplies of basic food supplies at certain times. The forecasting method that will be used in this research is Fuzzy Time Series (FTS) with the aim of overcoming this problem by estimating sales of goods (basic necessities) at UD. Ridho in Dolok Masihul. The results obtained are a system that was built to predict sales of basic food ingredients at UD. Ridho in Dolok Masihul is suitable for use so it is hoped that it can help UD owners. Ridho in determining the amount of basic food supplies in the future correctly so that UD. Ridho did not experience any losses or reduced income.